1982
DOI: 10.1084/jem.156.6.1615
|View full text |Cite
|
Sign up to set email alerts
|

In vitro regulation of IgA subclass synthesis. I. Discordance between plasma cell production and antibody secretion.

Abstract: In all normal individuals, the IgA in the serum and secretions can be divided into two subclasses, IgAa and IgA~, on the basis of antigenic differences. IgAa constitutes 80-90% of the IgA in serum (1-3), whereas approximately equal amounts of IgA1 and IgA2 occur in the secretions (2).Our previous studies have shown that although the IgA B cell distribution in the peripheral circulation reflects serum ratios of IgAa to IgA2, that is, 80% of the cells express surface IgA1 and 20% bear IgA2 (4), the differentiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

1983
1983
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 11 publications
3
10
0
Order By: Relevance
“…This is in accordance with the observed intestinal adaptation in relation to bacterial exposure, with increased IgA2 and decreased IgM production by lamina propria PCs (Kett et al, 1995). Sequential switching from IgA1 to IgA2 was observed neither in the colon (Lin et al, 2014) nor in pokeweed mitogen-stimulated peripheral blood lymphocytes (Conley and Bartelt, 1984).…”
Section: Regionalized Ig Class-switch Mechanismssupporting
confidence: 77%
“…This is in accordance with the observed intestinal adaptation in relation to bacterial exposure, with increased IgA2 and decreased IgM production by lamina propria PCs (Kett et al, 1995). Sequential switching from IgA1 to IgA2 was observed neither in the colon (Lin et al, 2014) nor in pokeweed mitogen-stimulated peripheral blood lymphocytes (Conley and Bartelt, 1984).…”
Section: Regionalized Ig Class-switch Mechanismssupporting
confidence: 77%
“…IgA synthesized by these circulating B lymphocytes express properties of IgA secreted by muco sal-associated lymphoid tissue with a predominant produc tion of polymeric IgA [22] and an equal proportion of IgA 1 and IgA2 [23]. We had previously demonstrated that the percentage of IgA 1 in serum and the k/A ratio of serum IgA 1 were unchanged during clinical exacerbation in pa tients with IgA nephropathy [10].…”
Section: Discussionmentioning
confidence: 99%
“…IgA-bearing cells were present in all family members studied (Table IV) (Table IV); mother (I-2) and daughter (II-2) showed only IgAl-containing blasts. In contrast, the plasmablasts of II-3 included IgAl-as well as IgA2-containing cells in a ratio as previously described (22,25 (6).…”
Section: Resultsmentioning
confidence: 99%